A Cost-Effective Pulse Oximeter Designed in Response to the COVID-19 Pandemic. Issue 1 (21st January 2021) - Metcalfe, Benjamin; Iravani, Pejman; Graham-Harper-Cater, Jonathan; Bowman, Richard; Stirling, Julian; Wilson, Peter
This paper introduces the design of a small and cost-effective optical pulse oximeter, including a finger clip, sensor readout electronics, and associated firmware. The device is based on widely-available commercial optical sensors that are designed for the wearables market and measure the reflection of different wavelengths of light. This design was produced in response to a request from the Royal United Hospital in Bath UK, in light of the severe shortage of clinical pulse oximeters during the 2020 COVID-19 pandemic. Products based on this design have not been submitted for medical device approval; the design documents here should be considered purely for research, educational and development purposes.